An Outstanding Career: Professor Emeritus Iacob Cătoiu - Octavian Oprică (Amfiteatru Economic)
Through the duration of his commissions of Deputy Dean (1981-1989) and, respectively, Dean (1992-2003), and also by the manner of approaching the managerial problems and his scientific extension, Professor Iacob Cătoiu left and indelible trace on the evolution of the former Department of Commerce in the Bucharest University of Economic Studies (ASE) – now the Department of Business and Tourism. He is author or co-author of an important number of books (57) and articles (105) and book presentations. Thus, after he made the personal acquaintance with Philip Kotler, the guru of international marketing, in 1997, Professor Iacob Cătoiu wrote the Forward to the Romanian version of Philip Kotler's volume Managementul marketingului (Marketing Management) a fundamental book in its field. (Nicolae Lupu)